2011
DOI: 10.1186/1476-511x-10-51
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of controlled porosity osmotic pump for Nifedipine and Metoprolol combination

Abstract: BackgroundA system that can deliver multi-drug at a prolonged rate is very important for the treatment of various chronic diseases such as diabetes, asthma and heart disease. Controlled porosity osmotic pump tablet (CPOP) system was designed to deliver Nifedipine (NP) and Metoprolol (MP) in a controlled manner up to 12 h. It was prepared by incorporating drugs in the core and coated with various types (PVP, PEG-400 and HPMC) and levels (30, 40 and 50% w/w of polymer) of pore former at a weight gain of 8, 12 & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Individual samples as well as a physical mixture of drug and excipients were weighed to about 5mg in DSC pan (Shimadzu DSC-50, Japan). The sample in the pan was scanned (Kumaravelrajan et al, 2011) in the temperature range of 50-300°C.The heating rate of 20°C min -1 was used and the thermogram obtained was reviewed for evidence of any interactions. Then the themograms were compared with pure samples versus optimized formulation.…”
Section: Compatibility Studies Dscmentioning
confidence: 99%
“…Individual samples as well as a physical mixture of drug and excipients were weighed to about 5mg in DSC pan (Shimadzu DSC-50, Japan). The sample in the pan was scanned (Kumaravelrajan et al, 2011) in the temperature range of 50-300°C.The heating rate of 20°C min -1 was used and the thermogram obtained was reviewed for evidence of any interactions. Then the themograms were compared with pure samples versus optimized formulation.…”
Section: Compatibility Studies Dscmentioning
confidence: 99%
“…7). Of the drug, 80% was released after 8,12, and 20 h with 20, 15, and 10% MS present in the coating layer. As the level of the pore former increased, the membrane became more porous after coming into contact with the aqueous environment, resulting in faster drug release from both the coating layer and the drug layer (11).…”
Section: Effect Of Pore Former Ms Levels On Drug Releasementioning
confidence: 99%
“…One technique involves adding partial immediate-release drug doses in the formulation, but additional processing steps are required that lead to two different release rates, which may be undesirable for mass production (9,10). Thin coatings around the dosage form is an alternative approach to provide highpermeability and fast initial release (11,12). However, the thin coating lacks strength and often bursts in use or provides insufficient protection to the dosage form which becomes vulnerable to damage during handling (2).…”
Section: Introductionmentioning
confidence: 99%
“…In this line of research, we reported controlled porosity osmotic pump [22] and sandwich osmotic pump tablet [23] for NP and MP combination.…”
Section: Introductionmentioning
confidence: 99%